Methotrexate-associated Epstein-Barr virus mucocutaneous ulcer: A case report and review of literature - Priyanka Yogendra Ravi; Elanthenral Sigamani; Yasir Jeelani; Marie Therese Manipadam (Wolters Kluwer Medknow Publications, 2018)
Epstein-Barr virus-positive mucocutaneous ulcer (EBVMCU) comprises part of the spectrum of B-cell lymphoproliferative disorders, reported in settings of immunosenescence and iatrogenic immunosuppression, affecting the oropharyngeal mucosa, skin, and gastrointestinal tract. We report a case of a 59-year-old female, known case of rheumatoid arthritis on methotrexate (MTX) for 15 years, who presented with an ulcer in the inner aspect of her cheek region for 2 years. Clinical examination revealed an infiltrative lesion involving the lower gingivobuccal sulcus of size 2 cm × 3 cm extending to the alveolus with level I lymph nodes, suspicious for carcinoma buccal mucosa. Anti-EBV-capsid antigen-immunoglobulin M and qualitative EBV polymerase chain reaction of peripheral blood were negative. Histopathological examination revealed atypical lymphoid cells with enlarged vesicular nuclei, prominent nucleoli, and moderate eosinophilic cytoplasm, few with binucleation (CD20 focally positive, CD79a focally positive, CD30+, EBV LMP-1+, MIB-I 60%) consistent with EBVMCU, MTX-associated. This is the first case report from India.